2015
DOI: 10.1016/s1995-7645(14)60345-x
|View full text |Cite
|
Sign up to set email alerts
|

Challenging loop—mediated isothermal amplification (LAMP) technique for molecular detection of Toxoplasma gondii

Abstract: The obtained results demonstrate that the LAMP technique has a greater sensitivity for detection of T. gondii. Furthermore, these findings indicate that primers based on the RE are more suitable than those based on the B1 gene. However, the B1-LAMP assay has potential as a diagnostic tool for detection of T. gondii.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…In addition, this assay was able to detect HBV‐DNA as low as 10 2 IU/mL and below. In earlier studies, better performance, ie 10‐ to 1000‐fold higher sensitivity of the LAMP assay than PCR was observed for the detection of Arcobacter species and Toxoplasma gondii …”
Section: Discussionmentioning
confidence: 95%
“…In addition, this assay was able to detect HBV‐DNA as low as 10 2 IU/mL and below. In earlier studies, better performance, ie 10‐ to 1000‐fold higher sensitivity of the LAMP assay than PCR was observed for the detection of Arcobacter species and Toxoplasma gondii …”
Section: Discussionmentioning
confidence: 95%
“…Behavioral changes attributed to infection due to T. gondii may be due to the parasite itself, which causes infection with nerve damage. IFN-γ, the main responsible cytokine for immunological defense against T. gondii is essential in all infected tissues, including the central nervous system (13)(14)(15)(16)(17). The biosynthesis of dopamine and/or serotonin could be directly affected by aromatic amino acid hydroxylases in T. gondii genome.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, tests with high sensitivity and specificity are required (19)(20)(21)(22)(23) T. gondii. They demonstrated that electrochemiluminescence is a useful method to detect T. gondii infection with high sensitivity and specificity of 97.1% and 100.0%, respectively (24).…”
Section: Discussionmentioning
confidence: 99%